Zooarchaeological analysis of an urban refuse dump in Cape Town's waterside at the turn of the 19th century - Graf, Otto Hermann Theodor (University of Cape Town, 2014)
Includes bibliographical references. === Zooarchaeology - the study of faunal remains - is not limited to prehistoric sites, but extends also into the realm of historical archaeology. Over the last two decades the number of papers and publications on a variety of aspects pertaining to zooarchaeology have grown. Although faunal research extends back into the mid-19 century, historical zooarchaeology has only increased over the last decade or so. This is equally the case in South Africa with historical zooarchaeology a growing avenue of research. This thesis provides a methodology through which fauna! material can be analyzed in-depth, beyond the mere appendices to site reports. Microscopic analysis of more than 2000 faunal specimens from a historical site within Cape Town (South Africa), Sea Street, was undertaken. The majority of the cultural material from this dump site dates to between c.1780 and c.1830. This time period covers the ending of the Verenigde Oostindische Companjie's (VOC) occupation of the Cape and its final succession to British rule in 1806. The explicit aim of this study was to go beyond minimum nwnbers (MNl) and number of identified specimens (NISP) to look at food-use patterns. A data sheet has been specifically constructed for this purpose. Other than looking at butchery style, the emphasis was to establish a ''general butchery pattern'', which explains how carcasses were utilized. This thesis only looks at domestic sheep, although the utilization of other domestic bvestock is also discussed. All faunal patterns are blurred by the possible inclusion of primary, secondary and tertiary butchery on one fauna! specimen. This does not include other cultural and natural formation processes which impact on the archaeological record. An attempt is made to distinguish between butchery done at the central locus and that away from it. Furthermore, an attempt is made to get at the cuts of meat that were actually acquired, not the erroneous results provided by lIINI totals. Statistical analyses, especially the Speannan rho rank order correlation coefficient, are used to evaluate discernible patterns, and establish the strengths or correlations of these patterns. As the recoverable faunal record does not include the unpreserved aspects of the original items that were consumed, an attempt is made to fill this gap left in the archaeological record through an analysis of available primary literature, especially diaries and newspapers. Complementary sets of information are also consulted so as to tie in with various aspects of the archaeological record.